Academy of Dental Materials guidance—Resin composites: Part I—Mechanical properties. Issue 8 (August 2017) - Ilie, N.; Hilton, T.J.; Heintze, S.D.; Hickel, R.; Watts, D.C.; Silikas, N.; Stansbury, J.W.; Cadenaro, M.; Ferracane, J.L.
Abstract: Objective: The objective of this project, which was initiated from the Academy of Dental Materials, was to review and critically appraise methods to determine fracture, deformation and wear resistance of dental resin composites, in an attempt to provide guidance for investigators endeavoring to study these properties for these materials. Methods: Test methods have been ranked in the priority of the specific property being tested, as well as of the specific test methods for evaluating that property. Focus was placed on the tests that are considered to be of the highest priority in terms of being the most useful, applicable, supported by the literature, and which show a correlation with clinical findings. Others are mentioned briefly for the purpose of being inclusive. When a standard test method exists, including those used in other fields, these have been identified in the beginning of each section. Also, some examples from the resin composite literature are included for each test method. Results: The properties for evaluating resin composites were ranked in the priority of measurement as following: (1) Strength, Elastic Modulus, Fracture toughness, Fatigue, Indentation Hardness, Wear—abrasion (third body) and Wear—attrition (contact/two body), (2) Toughness, Edge strength (chipping) and (3) Wear determined by toothbrush. Significance: The following guidance is meant to aid the researcher in choosing the proper method to assess key properties of dental resin composites with regard to their fracture, deformation and wear resistance.